2013
DOI: 10.2527/jas.2012-5851
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Saccharomyces cerevisiae fermentation product on in vitro fermentation and microbial communities of low-quality forages and mixed diets1

Abstract: Two experiments were conducted to investigate the effects of a Saccharomyces cerevisiae fermentation product (XP, Diamond V, Cedar Rapids, IA) on in vitro ruminal fermentation of single forage and mixed diets. In Exp. 1, an in vitro test was used to determine the effects of various concentrations (0, 1, 2, and 3 g/L) of XP on ruminal fermentation of the major forage sources of China (rice straw, RS; corn stover, CS; corn silage without grain, CSNG; and corn silage with grain, CSG). Total VFA reached a peak at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
58
2
5

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 67 publications
(73 citation statements)
references
References 25 publications
6
58
2
5
Order By: Relevance
“…Paulus et al (2012) and Mao et al (2013) documented the positive effects of S. cerevisiae on ruminal fermentation and microbial activities. A number of specific hypothetical biochemical mechanisms have been developed to explain the stimulatory effects of S. cerevisiae in the rumen (Chevaux and Fabre, 2007).…”
Section: Gas Production Rumen Fermentation and Degradabilitymentioning
confidence: 99%
See 4 more Smart Citations
“…Paulus et al (2012) and Mao et al (2013) documented the positive effects of S. cerevisiae on ruminal fermentation and microbial activities. A number of specific hypothetical biochemical mechanisms have been developed to explain the stimulatory effects of S. cerevisiae in the rumen (Chevaux and Fabre, 2007).…”
Section: Gas Production Rumen Fermentation and Degradabilitymentioning
confidence: 99%
“…For the in vitro model, the substrate amount relative to the rumen liquid volume is much less than in the rumen of a cow (<1 vs 12%). Therefore, when a rumen modulator like S. cerevisiae is supplemented at a different rate, it could change the fermentation rate and cause different substrate depletion, resulting in different response as the fermentation length is changed (Mao et al, 2013). Lila et al (2004) found variable effects of S. cerevisiae on ruminal fermentation when different substrates were used in vitro.…”
Section: Gas Production Rumen Fermentation and Degradabilitymentioning
confidence: 99%
See 3 more Smart Citations